2009
DOI: 10.1128/mcb.01737-08
|View full text |Cite
|
Sign up to set email alerts
|

CHIP Represses Myocardin-Induced Smooth Muscle Cell Differentiation via Ubiquitin-Mediated Proteasomal Degradation

Abstract: Myocardin, a coactivator of serum response factor (SRF), plays a critical role in the differentiation of vascular smooth muscle cells (SMCs). However, the molecular mechanisms regulating myocardin stability and activity are not well defined. Here we show that the E3 ligase C terminus of Hsc70-interacting protein (CHIP) represses myocardin-dependent SMC gene expression and transcriptional activity. CHIP interacts with and promotes myocardin ubiquitin-mediated degradation by the proteasome in vivo and in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 40 publications
7
76
0
Order By: Relevance
“…It will be very important to assess UBR5 expression or mutation in the smooth muscle cells of atherosclerotic plaque in human patients as this may provide important clinical correlations to these basic and translational observations. Previous studies have demonstrated myocardin expression can be tightly regulated by proteasome-mediated degradation (27,36). For example, the E3 ligase COOH terminus of Hsc70-interacting protein has been found to interact with the COOHterminal transactivation domain of myocardin and repress myocardin-dependent SMC gene expression by promoting degradation of myocardin protein.…”
Section: Discussionmentioning
confidence: 99%
“…It will be very important to assess UBR5 expression or mutation in the smooth muscle cells of atherosclerotic plaque in human patients as this may provide important clinical correlations to these basic and translational observations. Previous studies have demonstrated myocardin expression can be tightly regulated by proteasome-mediated degradation (27,36). For example, the E3 ligase COOH terminus of Hsc70-interacting protein has been found to interact with the COOHterminal transactivation domain of myocardin and repress myocardin-dependent SMC gene expression by promoting degradation of myocardin protein.…”
Section: Discussionmentioning
confidence: 99%
“…118 Additionally, the mind bomb (MIB) family of ubiquitin ligases are essential for Notch signaling by mediating the internalization ubiquitination and degradation of membranous Delta. 109 Conversely, several E3 ligases for Notch have been identified. Fbxw7 targets Notch to the proteasome for degradation in the vasculature, 119 in addition to its well-characterized negative regulation of apoptotic JNK signaling in neurons.…”
Section: E3-ligases Within the Notch Pathwaymentioning
confidence: 99%
“…107 Such an antip53 approach was associated with prevention of myocardial apoptosis and improved LV remodeling. In addition to p53, CHIP also mediates the degradation of myocardin, a key transcription factor of serum response factor, thereby decreasing smooth muscle cell differentiation, 109 and mediates the degradation of FoxO1 (as does Atrogin/MAFbx). Overexpression of CHIP represses FoxO1-mediated transactivation and its proapoptotic function after tumor necrosis factor-α treatment, whereas CHIP knockdown enhances FoxO1-mediated transactivation and its effect on SMC proliferation and survival.…”
Section: Terminus Of Hsc70-interacting Proteinmentioning
confidence: 99%
“…Although myocardin is considered as a critical component of the contractile "switch" in SMC, the signals that regulate myocardin are only partially understood. Extracellular signals can mediate this molecular switch through alterations in effector pathways, and indeed myocardin-mediated gene activation is regulated by ligands such as TGF␤1 and angiotensin II (16), as well as intracellular signal transduction mediators such as YAP1, glycogen synthase kinase 3 (GSK3), and extracellular signal-regulated kinase (ERK) and the C terminus of Hsc70-interacting protein (ChIP) (17)(18)(19)(20). Although the regulation of myocardin gene expression has been widely explored, there are few studies that address the cellular signal pathways underlying the regulation of myocardin-mediated SMC phenotypic changes.…”
mentioning
confidence: 99%